Executive Compensation and Value of Listed Deposit Money Banks in Nigeria - Barde, Ibrahim Magaji; Kantudu, Aliyu Suleiman; Dandago, Kabiru Isa; Jalingo, Ummu Ahmed; Zik-Rullahi, Ahmed Abubakar; Yusuf, Abubakar; Maigoshi, Zaharaddeen Salisu; Gololo, Ibrahim Aliyu; Suleiman, Bashir Ali (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
The increasing failure of banks has made it important to seek for ways to enhance its value in order to attract investors and potential investors. To make this reality, scholars have argued from various quarters that the people who manage the banks must be adequately compensated if the desired value needs to be achieved. Therefore, the study examines the relationship between executive compensation and value of listed deposit money banks (DMB) in Nigeria. The study adopted correlational research design with balanced panel data of 14 listed banks which served as population of the study for the period of 2010-2021 using Generalized Least Square (GLS) regression as a tool of analysis. The study found that CEO Pay and Chairman’s compensation have positive effect on the value of listed banks, while the highest paid director exact negative influence on the banks’ value. This implies that the CEO Pay and Chairman’s compensation improves the value of banks. Therefore, it is recommended among others that the management of banks should increase the CEO pay and place more emphasis on performance as a basis of increased pay to guarantee continuous improvement in the value of the banks.